Penegakan Hukum Terhadap Illegal Fishing dan Overfishing Sumberdaya Perikanan : (Dalam Aspek Pertahanan Negara) - Nurwidya Kusma Wardhani; Irwan Triadi (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2023)
This study aims to examine how law enforcement against illegal fishing and overfishing in the Indonesian ocean region is carried out by "Foreign Countries" such as Malaysia, Vietnam and other countries. We know that marine resources, in this case fisheries in Indonesia, are one form of the country's "defense" aspects. Indonesia's Exclusive Economic Zone or called ZEEI in the North Natuna Sea is an area that is often the case. For example, Indonesia there will be arrests of Vietnamese – flagged fishing vessels in early 2023 and until November 2018 the Indonesian Government had handled 134 illegal fishing cases and 41 of them had permanent legal force. Illegal fishing itself is often associated with large-scale fishing or overfishing thatresults in damage to the underwater ecosystem. Underwater ecosystems will become extinct if illegal fishing and overfishing cases are not seriously handled by the Government and Law Enforcement Officials. Foreign ships of illegal fishing and overfishing can be sanctioned in the form of violations of Law Number 31 of 2004 concerning Fisheries as amended by Law Number 45 of 2009 with the threat of a maximum prison sentence of 6 years and a maximum of Rp 20 billion rupiah. Also in the 1945 Constitution of the Republic of Indonesia mandates in article 27 paragraph (3) and article 30 paragraph (1) that state defense and security are the rights and obligations of each citizen to participate in the national defense and security effort and defending the country. The data collection method